Enhancement of antifouling of ultrafiltration polyethersulfone membrane with hybrid mg (oh)2/chitosan by polymer blending - Fathanah, U. (Amirkabir University of Technology - Membrane Processes Research Laboratory, 2020)
One of the most straight-forward approaches to improve the membrane performance is by imposing the hydrophilic property. This paper discusses the fabrication of polyethersulfone (PES)-based membranes using chitosan and Mg(OH)2 as organic and inorganic additives with the specific aim of increasing membrane hydrophilicity, respectively. Three variants of dope solutions were prepared with the addition of 1 wt chitosan, 1 wt Mg(OH)2 and a combination of chitosan/Mg(OH)2 into three different PES polymer solutions. The effects of additives on the resulting membranes were evaluated in terms of chemical functional groups by ATR-FTIR, morphological changes by SEM, and hydrophilicity degree of membrane surface based on the water contact angle (WCA), as well as the filtration profile, and antifouling properties. SEM images shows that the presence of additives altered the morphological structure of the membrane. It also enhanced the hydrophilicity significantly as shown by decreasing WCA from 84.2° to 68°. The modification also brings notable effects on the membrane performance as proven by the enhanced permeability of both pure water and humic acid (HA) solution as well as acceptable rejection of the HA solute. Overall, the Mg(OH)2-modified PES membrane produces much greater permeability and antifouling property compared to the rest thanks to its good hydrophilicity. © 2020 MPRL.